Nuclear sperm quality in total polymorphic teratozoospermia and its impact on intracytoplasmic sperm injection outcome. (28th February 2019) - Braham, Asma; Ghedir, Houda; Zidi, Ines; Sallem, Amira; Hajlaoui, Amani; Ajina, Mounir; Saad, Ali; Ibala‐Romdhane, Samira
Abstract: Various nuclear sperm alterations are reported in patients with syndromic teratozoospermia; however, this has not been clearly identified yet in total polymorphic teratozoospermia. The aim of this study was to analyse sperm aneuploidy, DNA integrity and chromatin packaging in 45 infertile patients with total polymorphic teratozoospermia, and to compare obtained results with those collected from 25 fertile men. For 14 patients, the impact of nuclear sperm abnormalities on intracytoplasmic sperm injection (ICSI) outcomes was analysed. Sperm chromatin condensation was evaluated using aniline blue staining, DNA fragmentation by TUNEL assay and chromosome abnormalities by FISH. The mean DNA fragmentation index was significantly higher in patients compared to controls, weakly and positively correlated to acrosome defects ( r  = 0.3; p  = 0.04) and positively and moderately correlated to microcephalic heads ( r  = 0.5; p  = 0.027). The aniline blue‐reacted spermatozoa rate was also high in comparison with controls, moderately and negatively correlated to progressive motility ( r  = −0.6; p  = 0.014). Total aneuploidy rate was considerably higher in our patients. A positive and moderate correlation was found between disomy Y rate and acrosome abnormalities ( r  = 0.5; p  = 0.048). These patients had an impaired sperm nuclear quality, which will affect the results in ICSI. Therefore, analysis of sperm chromatin condensation, DNA integrity and aneuploidy in such cases is very useful before ART.